2020
DOI: 10.1515/hmbci-2020-0007
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of military physical exercise on irisin concentrations and oxidative stress among male healthy volunteers

Abstract: BackgroundIrisin, a newly discovered hormone, is secreted into the circulation from skeletal muscles in response to physical exercise. The biochemical parameters related to irisin secretion have not been sufficiently investigated yet. The aim of this study was to examine the effectiveness of exercise on the level of irisin and its correlation with biochemical and oxidative stress parameters.Materials and methodsIn this pre- and post-test observational study, 39 healthy male volunteers from a military training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
0
2
0
2
Order By: Relevance
“…Several kinds of physical exercise increased irisin blood levels among healthy people as well. High-intensity interval training increased irisin in young, healthy males [41,60] and healthy young adults [43], military aerobic training [48] increased irisin blood levels in young, healthy males and one study with a single group design found a significant increase in irisin in young females after treadmill exercise [37]. On the other hand, cycle ergometer-sprint training, consecutive training [77] as well as indoor running [64] led to a decrease of irisin blood levels in young, healthy males, and the same effect was found after basketball training in healthy children [39] or after taekwondo training in obese children [70].…”
Section: Summary Of Main Results and Interpretationsmentioning
confidence: 94%
“…Several kinds of physical exercise increased irisin blood levels among healthy people as well. High-intensity interval training increased irisin in young, healthy males [41,60] and healthy young adults [43], military aerobic training [48] increased irisin blood levels in young, healthy males and one study with a single group design found a significant increase in irisin in young females after treadmill exercise [37]. On the other hand, cycle ergometer-sprint training, consecutive training [77] as well as indoor running [64] led to a decrease of irisin blood levels in young, healthy males, and the same effect was found after basketball training in healthy children [39] or after taekwondo training in obese children [70].…”
Section: Summary Of Main Results and Interpretationsmentioning
confidence: 94%
“…Sekiz haftalık sürede Tabata protokolünü uygulayan HIIT antrenman grubunun (n=15) egzersiz bitiminden 1 gün sonra, kan irisin konsantrasyonunda anlamlı artış olduğu bildirilmiştir [17]. Askeri eğitim ortamındaki 39 sağlıklı erkeğin, 8 hafta süren egzersiz eğitiminin bitiminden sonraki gün irisin salgılanmasının arttığı gözlenmiştir [16]. Jedrychowski ve ark.…”
Section: Serum İrisin Düzeylerinin Elisa Yöntemi Ile öLçümüunclassified
“…Egzersize yanıt olarak irisin seviyelerinin akut olarak [2,7,[12][13][14] ve kronik egzersizden 1 gün sonra toparlanma döneminde arttığı [15][16][17][18] bildirilmiştir. Egzersiz sonrası FNDC5 seviyelerinde de artışın gözlendiği çalışmalar mevcuttur [2,19].…”
Section: Introductionunclassified
“…Different tissues have different emissivity at infrared wavelengths, emitting signals 15,16 . Objects naturally emit thermal signals in the range of infrared electromagnetic radiation, and the type of signal emitted or radiated at a certain temperature depends on both the characteristics of the object and its surrounding environment 17 , just like the technology that captures these signals and transforms them into images 18 , Therefore, infrared measurement devices acquire the radiation emitted by the object and convert it into an electronic signal 19,20 . When a cell performs a biological task ATP hydrolysis takes place resulting in the loss of energy in the form of heat 21 .…”
Section: Introductionmentioning
confidence: 99%